Exploring Challenges and Opportunities in Online Learning Among EFL Students in Higher Education - Isma, Adi; Suwandi, Edi; Sudewi, Putu Wahyu; Ridwan, Ridwan (Journal of Languages and Language Teaching, 2025)
Online learning has become an essential part of higher education, offering flexibility and wider access to students worldwide. Yet, in practice, many learners, especially those in EFL contexts, continue to face significant challenges that are often overlooked in existing research. This descriptive quantitative study explores the challenges and opportunities of online learning for English as a Foreign Language (EFL) students in higher education, specifically focusing on the English Department at Universitas Sulawesi Barat, Indonesia. Using a cross-sectional survey of 85 students, the research aimed to identify common obstacles and advantages in online learning while uncovering students' expectations and suggestions. The results revealed that technical issues (87.1%), lack of social interaction (67.1%), and difficulty understanding course material (52.9%) were the primary obstacles faced by students. Conversely, cost-effectiveness (62.4%), unrestricted access to course materials (49.4%), and reduced social demands (42.4%) were identified as key advantages. Notably, 79% of respondents expressed reluctance to engage in future online learning. This sentiment reflects persistent structural and pedagogical gaps. To improve the online learning experience, students proposed enhanced technological infrastructure, more interactive engagement, and increased instructional support. The findings underscore the need for institutions to reevaluate their online education strategies to ensure student-centered and sustainable learning environments.